Evaluation of left atrial volume and function in patients with coronary slow flow phenomenon using real-time three-dimensional echocardiography - Xing, Yumeng; Chen, Yongle; Liu, Yu; Kong, Dehong; Yan, Yan; Shu, Xianhong; Pan, Cuizhen (The International Journal of Cardiovascular Imaging, 2019)
This study aimed to evaluate the left atrial (LA) volume and phasic functions using real-time three-dimensional echocardiography (RT3DE) in coronary slow flow phenomenon (CSFP) patients with preserved left ventricular ejection fraction (LVEF). 56 patients with CSFP (36 males, 20 females) and 48 controls with normal coronary flow (27 males, 21 females) were prospectively enrolled. Comprehensive transthoracic echocardiographic examination and RT3DE for the assessment of LA dynamics were performed in all participants. LA maximum, minimum, and pre-atrial contraction volumes (LAV-max, LAV-min, and LAV-preA) were obtained for every subject. Conventional echocardiographic parameters, except for isovolumetric relaxation time and transmitral deceleration time, did not differ in two groups. RT3DE demonstrated higher LAV-max, LAV-min, LAV-preA, indexed LAV-max (LAVi-max), LA total emptying volume, and LA active emptying volume and fraction for CSFP patients compared with controls (all P < 0.05). In addition, LA total emptying fraction and LA passive emptying fraction were found to be lower in CSFP patients than in controls (all P < 0.05). Moreover, there were positive correlations between mean thrombolysis in myocardial infarction frame count values and LAV-max, LAV-min, LAV-preA, LAVi-max, and LA total and active emptying volumes. CSFP was associated with enlarged LA volumes, impaired LA reservoir and conduit function and enhanced contractile function. Evaluation of LA dynamics using RT3DE could facilitate recognition of subtle myocardial alterations related with CSFP.